Functional Outcomes after Inpatient Rehabilitation in a Prospective Stroke Cohort. (September 2013) - Ng, Yee Sien; Astrid, Suantio; De Silva, Deidre Anne; Tan, May Leng Dawn; Tan, Yeow Leng; Chew, Effie
Aim: Rehabilitation is proven to improve function following a stroke. The functional outcomes of stroke patients and benefits from rehabilitation are highly variable. We aim to describe functional outcomes and gains following inpatient rehabilitation post-stroke and identify factors associated with improved outcomes. Methods: In this five-years prospective study, data for 1332 consecutive stroke patients admitted to the Singapore General Hospital inpatient rehabilitation unit were charted into a custom-designed rehabilitation database. The primary outcome measure was the Functional Independence Measure (AFIM) and discharge (DFIM). The functional gain was defined as the DFIM-AFIM. Results: The mean age was 64.1±12.5 years, 58.9% were male patients and 78.9% consisted of ischaemic (versus haemorrhagic) strokes. The average rehabilitation length of stay (RLOS) was 18.7±13.9 days and the majority (87.7%) were discharged home. The most common risk factor was hypertension (78.4%) and urinary tract infection (21.2%) was the commonest post-stroke complication. The mean AFIM and DFIM scores were 67.9±23.0 and 83.2±23.5 respectively with a mean functional gain of 15.4±12.3 FIM points. Younger, male, and haemorrhagic stroke patients had better functional outcomes. Multiple regression analysis results revealed that higher DFIM score was associated with higher admission motor and cognitive FIM scores, younger age, male gender, employment at admission, single patients, presence of a caregiver, haemorrhagic stroke, right-sided motor impairments, absence of urinary tract infection or depression, acupunction treatment, and a longer RLOS. The regression model on functional gain was associated with similar independent predictors on DFIM scores except that a higher AFIM was associated with lower functional gains. Conclusion: In this large cohort study, stroke patients make significant functional gains and should be offered rehabilitation to improve outcomes. A comprehensive set of multiple interacting demographic, clinical, cultural, and social factors significanctly impact on stroke functional outcomes after inpatient rehabilitation. The identification of these factors allows optimising rehabilitation for individual patients, and is important for discharge and resource planning.